Pressure-relief and anti-impact technology of near-fault blasting by high-level roadway in deep pressure bumps mine - REN Wentao; WANG Hao; YU Bingbing; ZUO Jinjing; GU Peng; ZHANG Yuantong; ZHENG Xingbo; WANG Bo; ZHANG Bin; WAN Xiao (矿业科学学报)
The prevention and control of rockburst under complex geological conditions is the focus of research on mining technology at this stage. Based on the 106-level high-energy microseismic events of Xinjulong Coal Mine and the high rockburst risk of faults in special positions, a new type of pressure-relief and anti-impact technology based on near-fault high-level blasting is proposed. Anti-rockburst effect of the new pressure relief blasting technology is comprehensively evaluated from multiple dimensions. The results show that: the maximum expansion radius of the explosive fracture zone obtained by in-situ monitoring was 1.5 m, and the hole bottom distance and the charge quantity designed accordingly can ensure the breaking effect of the fault; the microseismic event of 104 energy level decreased from 5.2 % before stopping mining to 1.5 % after recovering mining, and no 105 and 106 energy level events occurred. Under the horizontal principal stress, the deformation of the roadway was larger than that of the roof and floor, and the stress of the overlying strata was transferred to the solid coal side, which led to the deformation of the solid side larger than that of the goaf side. The stress fluctuation range of the surrounding rock of the roadway was reduced from 6 ~ 12.85 MPa to 6 ~ 8.5 MPa, and the peak value was significantly reduced by 40 %. The fracture zone area formed by the high-level near-fault pressure-relief blasting effectively cut off the connection between the fault and the thick and hard roof, weakened the influence of the "seesaw" effect. The result has important application significance for the practice of anti-rockburst and pressure-relief engineering and the treatment of rockburst disasters.